Barriers to antenatal care during COVID-19 pandemic: A hospital-based retrospective cross-sectional study in rural south Karnataka - Philomena Zacharias; Merlyn Joseph; Ann Jacob; Mary Viji CL; Nitisha Ann Josy; Shulia Lydia; Avita Rose Johnson (Barpeta Obstetrics and Gynaecological Society, 2021)
Background: As part of Covid-19 pandemic response, India went into lockdown to reduce transmission and prevent overwhelming of hospitals. Pregnant women need protection from Covid-19, while ensuring they receive antenatal care (ANC). Objectives: To assess barriers to ANC during Covid-19 pandemic lockdown in rural south Karnataka. Methods: Hospital-based, retrospective cross-sectional study among pregnant women availing ANC in June-July 2020, using a pre-tested interview schedule to capture barriers of access and fears during the pandemic lockdown of 22 March to 31 May 2020. Chi-square test performed to associate barriers to ANC with various independent co-variates. Results: Of 144 pregnant women, 61.8% reported at least one barrier to accessing ANC, 38.9% reported at least one fear and 85% were not able to access ultrasounds and blood tests. Barriers were lack of income, lack of transportation and hospitals /diagnostic centres remaining closed. Barriers of fear were: getting infected with Covid-19, fear of not receiving proper treatment, fear of being turned away from hospital and fear of isolation from family. Women of lower socio-economic class and with pre-existing pregnancy complications were significantly more likely to experience barriers to ANC. Conclusion: Our study found that those residing in rural areas faced barriers to ANC as a result of a well-intentioned pandemic response. Community-based strategies, mechanisms for referral, health education and counselling through village-level workers may help to overcome these barriers. Policy makers must prioritize needs of pregnant women and address these barriers to ensure continued accessibility to ANC during any future pandemics.